Academic writing course evaluation: Perspective of engineering students - Balakrishnan, Subatira; Abd Halim, Noor Baiduri; Hamdzah, Nor Lailatul Azilah; Mokhtar, Siti Aisyah (Universiti Malaysia Perlis, 2022)
Engineering education has now put emphasis on writing skills that is considered equally important in shaping competent engineers. Academic Writing as an English for Specific Purposes (ESP) course equips students with essential writing skills for engineering academic and professional tasks. This study is undertaken with the aim to investigate the strengths and weaknesses of the current Academic Writing course offered at a technical university. The findings are crucial for the course's continuous improvement. This paper will report quantitative data through the questionnaire method employed that involves the feedback of 100 enrolled students. It comprises four dimensions namely course contents, materials and resources, testing and assessment, and academic instruction. The results reveal some constructive feedback from students that includes the need to improve in course materials and resources due to lack of study materials, as well as a call for the academic instruction by instructors to be improved. Suggestions and recommendations are made in order to contribute to continuous quality improvement for the course.